Operationalizing Digital Infrastructure for Nigerian SME Empowerment via Community-Based Service Learning - Salisu Abdullahi; Maryam Muhammad Sabo; Ali Nuhu Abubakar; Hadiza Nasir Iro (Help: Journal of Community Service, 2026)
Despite national macroeconomic efforts to improve Nigeria's Ease of Doing Business (EoDB) through regulatory reforms and digital infrastructure investments, economic formalization remains inconsistent at the grassroots level. This stagnation is largely due to a significant gap in digital literacy and the underutilization of e-governance tools by micro, small, and medium enterprises (SMEs). This community service project aimed to bridge this macro-micro divide by operationalizing digital infrastructure to empower local SMEs through targeted digital capacity building. Utilizing a Community-Based Service Learning (CBSL) approach, the project integrated academic frameworks with practical community intervention. The program engaged 150 SME owners in Kano State, Nigeria. The intervention comprised a three-day intensive technical workshop followed by a one-month, one-on-one mentorship phase. Training focused on navigating online government business registration portals and integrating mobile digital payment systems. Program efficacy was evaluated utilizing pre- and post-intervention surveys alongside qualitative participant observations. The CBSL intervention yielded significant, measurable improvements in digital adoption and entrepreneurial self-efficacy. Post-intervention data indicated that 82% of participants successfully registered their enterprises online, compared to a baseline where only 18% possessed basic portal navigation skills. Additionally, the cohort demonstrated a 65% increase in the active adoption of mobile digital payment applications. Qualitatively, participants reported a 90% increase in confidence regarding regulatory compliance and formal business administration.